Metode Implementasi Pembelajaran Hafalan Al-Qur’an di MDA At-Taqwa Desa Gung Pinto - Yogi Karmelta Ketaren; Nur Maulida; Syazkia Salsabila Rais; Nur Afifa Daulay; Ahmad Syukri Sitorus; Intan Wahyuni Hasibuan; Suriani Sitorus; Miftahul Jannah (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
The purpose of this research is to compile and synthesize information about the planning, implementation, and evaluation of teaching the Arabic lexicon contained in the Al-Qur'an. This study adopted a qualitative methodology, collecting information through observation, interviews, and written notes. Collection, reduction, presentation, and data extraction are part of the data analysis method. In data analysis, source and method triangulation is a very important step. This research shows that MDA AT-TAQWA DESA GUNG PINTO is home to people who have the desire and desire to study the Qur'an in an interpretive and linguistic way, making this kind of learning planning a competitive advantage. This instructional plan is divided into four parts: objectives, content, methodology, and evaluation. The teacher uses the reading by listening method, pays attention to students' fluency and understanding when reading; in the second stage, students maintain a consistent and advanced understanding of the Qur'an through the use of listening-reading techniques, both with their teacher and among themselves. Keywords: Implementation Methods, Learning, Memorizing the Qur’an